SEO for Dummies - Kent, Peter (John Wiley & Sons, Incorporated, 2020)
Up relevance scores, improve page speed, optimize voice search questions, and more!   Search Engine Optimization For Dummies shows website owners, developers, and search engine optimizers (SEOs) how to create a website that ranks at the top of search engines and has high-volume traffic, while answering the essential question of "how do I get people to visit my site?" By understanding search engine basics (what are they, which ones are important, how to get started), building a search engine-friendly site, registering your site with directories and indexes, using analysis tools to track results and link popularity to boost rankings, and advertising your site by using pay-per-click options, you can use the tricks of SEO masters to drive traffic to your site. You'll also discover how to write effective content, use social media to boost your profile, and manage your platform and reputation to positively impact your search engine rankings. Develop a search strategy and use new SERP features Maximize the effects of personalized search Analyze results with improved analytics tools Optimize voice search strategies There's no time like the present to create a website that ranks at the top of search engines and drives traffic to your site with these tips, tricks, and secrets.